2023
DOI: 10.1001/jamaophthalmol.2023.2260
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Aflibercept Biosimilar SB15 in Neovascular Age-Related Macular Degeneration

Abstract: ImportanceAflibercept biosimilars can expand available treatment options in retinal diseases and have the potential to improve patient access to safe and effective therapy.ObjectiveTo establish equivalence in efficacy and similarity in safety, pharmacokinetics, and immunogenicity of SB15 and reference aflibercept (AFL) in neovascular age-related macular degeneration (nAMD).Design, Setting, and ParticipantsThis was a randomized double-masked parallel group phase 3 trial conducted at 56 centers in 10 countries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Aflibercept biosimilars are also underway of development, with MYL-1710 (Momenta Pharmaceuticals and Mylan) being investigated for DME and ALT-L9 (Altos Biologics), FYB-203 (Formycon), SB-15 (Samsung Bioepis), and SCD-411 (Sam Chun Dang Pharmaceuticals) for nAMD. A recent phase III trial published in July 2023 successfully showed no clinically significant differences between SB-15 (n=224) and aflibercept (n=225) with regard to both efficacy and safety profile in patients with nAMD 27 . The primary endpoint of this trial was a change in BCVA from baseline after 8 weeks, and secondary endpoints were BCVA and CST changes at 32 weeks, safety and PK profiles, and immunogenicity 27 .…”
Section: Current Biosimilar Market and Pipeline Therapeutics Within O...mentioning
confidence: 87%
See 2 more Smart Citations
“…Aflibercept biosimilars are also underway of development, with MYL-1710 (Momenta Pharmaceuticals and Mylan) being investigated for DME and ALT-L9 (Altos Biologics), FYB-203 (Formycon), SB-15 (Samsung Bioepis), and SCD-411 (Sam Chun Dang Pharmaceuticals) for nAMD. A recent phase III trial published in July 2023 successfully showed no clinically significant differences between SB-15 (n=224) and aflibercept (n=225) with regard to both efficacy and safety profile in patients with nAMD 27 . The primary endpoint of this trial was a change in BCVA from baseline after 8 weeks, and secondary endpoints were BCVA and CST changes at 32 weeks, safety and PK profiles, and immunogenicity 27 .…”
Section: Current Biosimilar Market and Pipeline Therapeutics Within O...mentioning
confidence: 87%
“…A recent phase III trial published in July 2023 successfully showed no clinically significant differences between SB-15 (n=224) and aflibercept (n=225) with regard to both efficacy and safety profile in patients with nAMD 27 . The primary endpoint of this trial was a change in BCVA from baseline after 8 weeks, and secondary endpoints were BCVA and CST changes at 32 weeks, safety and PK profiles, and immunogenicity 27 . Formycon recently announced the submission of a BLA for another aflibercept biosimilar, FYB-203; a decision is expected by late August 2023.…”
Section: Current Biosimilar Market and Pipeline Therapeutics Within O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute, severe, sterile IOI after intravitreal injections have been reported with many commonly used anti-VEGF agents, including aflibercept and ranibizumab . More recently, this type of IOI as well as relatively rare reports of acute severe IOI associated with occlusive retinal vasculitis have been reported with more recently approved intravitreal agents for retinal diseases, including brolucizumab, pegcetacoplan, and faricimab as well as biosimilar agents ranibizumab and aflibercept . Nevertheless, these clinical trial reports, including those for faricimab, have reported infrequent severe IOI events .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, this type of IOI as well as relatively rare reports of acute severe IOI associated with occlusive retinal vasculitis have been reported with more recently approved intravitreal agents for retinal diseases, including brolucizumab, pegcetacoplan, and faricimab as well as biosimilar agents ranibizumab and aflibercept . Nevertheless, these clinical trial reports, including those for faricimab, have reported infrequent severe IOI events . Inflammatory complications following intravitreal anti-VEGF injections that are sterile are characterized by acute-onset IOI without infection that resolve without antibiotic treatment .…”
Section: Discussionmentioning
confidence: 99%